La mecanización agrícola como medio para la optimización de recursos y su influencia sobre la productividad en los cultivos de tomate riñón, papa y maíz en el cantón Chambo durante el periodo 2012-2015. - Rivera Heredia, Patricio Adrian (2017)
The present research on agricultural mechanization as a means for the optimization of resources and the influence on the productivity of tomato, kidney and potato crops in Chambo Canton, has as main objective to analyze and verify the behavior of mechanization, taking into account Account the different factors involved in the production processes of each crop. For which it was necessary the application of surveys that revealed the costs incurred by each producer to make production efficient, in which indirect costs and direct costs were considered, the latter having a subgroup that includes hand Of work, machinery and equipment and supplies. All the information gathered in these instruments, is made known through tables and graphs in which the gathered information is included; So the content of the research is composed of four chapters, briefly detailed below:Chapter I, Referential Framework, contains the problem statement, formulation of the problem, general and specific objectives, and the justification and importance of the research, while observing the problem that gives rise to research and the objectives that Is sought to fulfill.Chapter II, Theoretical Framework, is composed of concepts, theories, methods and techniques that support the theory of induced innovations, while deepening the definition, classification and characteristics that support the variables involved.Chapter III, Methodological Framework, encompasses the methodology used in the present research, the analysis of each of the indicators generated in the same way are the results obtained in the econometric model applied in the SPSS program to determine the incidence of the Variables.Chapter IV contains the concussions to which the research process was completed and the recommendations to be considered in order to contribute to the improvement of production processes in the agricultural sector